Soft Skills na Indústria 4.0 - Penhaki, Juliana de Rezende (2019)
Impacted by Industry 4.0, the labor market is changing. Soft Skills are classified as very important skills in the modern work environment, as they can help the demands of technological expansion, structural organizational change, integration of geographically dispersed businesses into global production networks, and the need to keep up of technological advances and respond to new developments in the market. The aim of this research is to characterize Soft Skills in the context of industry 4.0. The research is applied and classified as descriptive. The data used comes from predominantly qualitative research. Analyses were based on secondary data collected via bibliometric and bibliographic research, the bibliographic research conducted the work and allowed access to the operationalization of the concepts, variables, and issues inherent to Soft Skills and industry 4.0. The data on Soft Skills and industry 4.0 will be cross-checked in order to identify the Soft Skills needed to introduce the professional in the industry. Finally, the data about Soft Skills and Industry 4.0 will be analyzed through the content analyses technical, in order to identify the Soft Skills for the integration of the professional in the Industry 4.0. The following Soft Skills were characterized in the Industry 4.0 framework: creativity, motivation, flexibility, communication, teamwork, leadership. Creativity 4.0, Motivation 4.0 , Flexibility 4.0, Communication 4.0, Teamwork 4.0, Leadership 4.0 were the results found after reflections and analysis on Industry 4.0 scenario.